The GMRT 150 MHz all-sky radio survey: First alternative data release TGSS ADR1 - Intema, Hubertus; Jagannathan, P.; Mooley, K.; Frail, D. (EDP Sciences, 2017)
We present the first full release of a survey of the 150 MHz radio sky, observed with the Giant Metrewave Radio Telescope (GMRT) between April 2010 and March 2012 as part of the TIFR GMRT Sky Survey (TGSS) project. Aimed at producing a reliable compact source survey, our automated data reduction pipeline efficiently processed more than 2000 h of observations with minimal human interaction. Through application of innovative techniques such as image-based flagging, direction-dependent calibration of ionospheric phase errors, correcting for systematic offsets in antenna pointing, and improving the primary beam model, we created good quality images for over 95 percent of the 5336 pointings. Our data release covers 36 900 deg2 (or 3.6 p steradians) of the sky between-53° and +90° declination (Dec), which is 90 percent of the total sky. The majority of pointing images have a noise level below 5 mJy beam-1 with an approximate resolution of 25''×25'' (or 25''×25''/cos(Dec-19°) for pointings south of 19° declination). We have produced a catalog of 0.62 Million radio sources derived from an initial, high reliability source extraction at the seven sigma level. For the bulk of the survey, the measured overall astrometric accuracy is better than two arcseconds in right ascension and declination, while the flux density accuracy is estimated at approximately ten percent. Within the scope of the TGSS alternative data release (TGSS ADR) project, the source catalog, as well as 5336 mosaic images (5°×5°) and an image cutout service, are made publicly available at the CDS as a service to the astronomical community. Next to enabling a wide range of different scientific investigations, we anticipate that these survey products will provide a solid reference for various new low-frequency radio aperture array telescopes (LOFAR, LWA, MWA, SKA-low), and can play an important role in characterizing the epoch-of-reionisation (EoR) foreground. The TGSS ADR project aims at continuously improving the quality of the survey data products. Near-future improvements include replacement of bright source snapshot images with archival targeted observations, using new observations to fill the holes in sky coverage and replace very poor quality observational data, and an improved flux calibration strategy for less severely affected observational data.